2015
DOI: 10.1016/j.jkss.2014.09.003
|View full text |Cite
|
Sign up to set email alerts
|

Case influence diagnostics in the lasso regression

Abstract: a b s t r a c tUsing the diagnostic results in the ridge regression model, we propose an approximate version of Cook's distance in the lasso regression model since the analytic expression of the lasso estimator is not available. Also, we express the proposed Cook's distance in terms of basic building blocks such as residuals and leverages. We verify that the proposed statistic successfully detects potentially influential observations on estimators of regression coefficients and on the model selection in the la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 27 publications
1
7
0
Order By: Relevance
“…By examining the various plots in Figures , we can gain better understanding of the impact of each influential observation on the estimated coefficients, as well as on the LASSO plot. The identification of the 69th, 95th, 96th and 97th observations as influential is similar to the results in Kim et al…”
Section: Influence Plots For Evaluating the Effect Of Influential Obssupporting
confidence: 89%
See 1 more Smart Citation
“…By examining the various plots in Figures , we can gain better understanding of the impact of each influential observation on the estimated coefficients, as well as on the LASSO plot. The identification of the 69th, 95th, 96th and 97th observations as influential is similar to the results in Kim et al…”
Section: Influence Plots For Evaluating the Effect Of Influential Obssupporting
confidence: 89%
“…Detecting influential observations should be an important part of model selection and fitting, because influential observations can greatly impact results and reduce the effectiveness of the LASSO method. Recently, Zhao et al suggested high‐dimensional influence measures, and Kim et al proposed case influence diagnostics for LASSO regression. A LASSO plot can be a useful graphical tool for finding variable selection patterns in the presence of multicollinearity.…”
Section: Introductionmentioning
confidence: 99%
“…Kim et al (2015) recently derived an approximate version of Cook's distance in the LASSO regression; however, it is based on the "large n, small p" assumption. Cook's distance in the LASSO model suggested by Kim et al (2015) cannot be directly used in high-dimensional data because the covariance estimator of the LASSO estimator, which is necessary in defining a version of Cook's distance, is not easily derived in the high-dimensional data. Further, under high dimensional setup, we are more interested in influential observations on the variable selection rather than the influence on estimators.…”
Section: Introductionmentioning
confidence: 99%
“…Diagnostic results in Box-Cox transformation model (Box and Cox, 1964) have also been done by Cook and Wang (1983), Hinkley and Wang (1988), Kim et al (1996), and Tsai and Wu (1990). Walker and Birch (1988) derived a version of Cook's distance in the ridge regression (Hoerl and Kennard, 1970), and Kim et al (2015) proposed a type of Cook's distance in the lasso regression model.…”
Section: Introductionmentioning
confidence: 99%